(untitled) (Journal of Economic Research & Business Administration, 2015)
Globalization trends have a significant impact on industrial sectors and socio – economic development of many countries. In this process of strengthening international relations and initiate new open national economies intensify interstate effects of some countries to other countries in the socio – economic policy. In these conditions, the main factor affecting world economy is international capital, in particular , impact of foreign direct investment, both in terms of internal and external flows. It shows both for developed and developing countries effective allocation and usage of foreign investment in a given country is largely determined by the efficiency of foreign investment activities of state, as well as large multinationals